2022
DOI: 10.1101/2022.07.06.498909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Correlates of Statistical Learning in Developmental Dyslexia: An Electroencephalography Study

Abstract: The human brain extracts statistical regularities from the surrounding environment in a process referred to as statistical learning. Recent behavioural evidence suggests that developmental dyslexia affects statistical learning. However, surprisingly few neurophysiological studies have assessed how developmental dyslexia affects the neural processing underlying statistical learning. In this study, we used electroencephalography to explore the neural correlates of an important aspect of statistical learning, sen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
2
0
1
Order By: Relevance
“…Contrary to a classical oddball paradigm where a change in the stimuli is instantly reflected in auditory memory responses, in the current paradigm a longer exposure time is required to learn the transitional probabilities. On this basis, detection of a statistical deviant engages a different cognitive mechanism than classical oddball stimuli [47][48][49] . Furthermore, a recent statistical learning study using EEG reported that brain responses elicited by statistical deviants had a more frontal scalp distribution than those elicited by location deviants 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to a classical oddball paradigm where a change in the stimuli is instantly reflected in auditory memory responses, in the current paradigm a longer exposure time is required to learn the transitional probabilities. On this basis, detection of a statistical deviant engages a different cognitive mechanism than classical oddball stimuli [47][48][49] . Furthermore, a recent statistical learning study using EEG reported that brain responses elicited by statistical deviants had a more frontal scalp distribution than those elicited by location deviants 48 .…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, detection of a statistical deviant engages a different cognitive mechanism than classical oddball stimuli [47][48][49] . Furthermore, a recent statistical learning study using EEG reported that brain responses elicited by statistical deviants had a more frontal scalp distribution than those elicited by location deviants 48 . This is in line with our findings showing stronger activations over the pre-SMA and premotor cortex compared to results from classical auditory oddball-studies.…”
Section: Discussionmentioning
confidence: 99%
“…Durante las tareas relacionadas con la lectura, las diferencias entre los niños disléxicos y los del grupo de control parecen estar más localizadas en los sitios temporoparietales izquierdos. Finalmente, Daikoku et al (2023) examinaron las correlaciones neurales de durante la transición de estímulos en individuos con DD. Los hallazgos indican que los mecanismos neurales subyacentes a la detección pre-atentiva de cambios acústicos y al aprendizaje auditivo implícito están afectados en la dislexia evolutiva.…”
Section: Eeg Y Diagnóstico De Enfermedades Neurológicasunclassified